Elucidating the Effects of Formalin as Food Preservative on Hematological Profile and Fertility of Swiss Albino Mice - Hasan, Md Tanvir; Akter, Saima; Roy, Dipu; Habiba, Umme; Khatun, Fahima; Hoque, Md Nazmul; Talukder, Anup Kumar; Rahman, Abu Nasar Md Aminoor; Haider, Md Golam; Islam, Md Taimur (Journal of Science and Technology Research, 2024)
In Bangladesh, the use of formalin as a food preservative has recently expanded significantly. With this backdrop, the study was attempted to discover changes in the fertility, gross structure, and histoarchitecture of the male reproductive system and hematology in Swiss albino mice as a result of formalin use. Up until experimental week 24, four groups of four mice each were given normal drinking water mixed with formalin at doses of 1%, 5%, 10%, and 20%, respectively, orally. A control group of mice (n=4) were given normal drinking water only. After 24 weeks of treatment, the testicular weight, sperm concentration, morphology, gonadosomatic index (GSI), and hematological profile were evaluated. Testicular histological changes were also evaluated. Formalin-treated mice had significantly lower testes weight, GSI, and sperm count (P<0.05) than the control group. In formalin-treated mice, hematocrit value (HCT) and hemoglobin (Hb) concentration were dramatically reduced; percentage of morphologically healthy epididymal sperm also reduced significantly. In the formalin-treated animals, histopathology indicated degenerative alterations in seminiferous tubules, a lower number of spermatogenic cells, the buildup of spermatozoa with exudates in the tubular lumen, and the displacement of the seminiferous tubule from the basement membrane. According to the findings, formalin has a negative impact on hematological profile and reproductive health of male mice. J. of Sci. and Tech. Res. 6(1): 73-81, 2024